(untitled) (Swiss Medical Weekly, 2017)
OBJECTIVES To report survival following different operative strategies and perioperative chemotherapy in patients with synchronous colorectal liver metastases in a tertiary academic referral centre. METHODS We performed a retrospective analysis, based on a prospective database, of patients who presented with synchronous colorectal liver metastases. Follow-up data were obtained from medical records, letters or telephone contacts. The main endpoint was overall survival. An additional event of interest was postoperative mortality according to treatment strategy. Predefined variables were analysed to identify associated risk factors. RESULTS Overall, 109 patients undergoing liver resection for synchronous colorectal liver metastases between 2000 and 2010 were identified. The majority of patients had resection of the primary tumour first (n = 82), the classic approach; notably fewer were treated according to a combined (n = 20) or a reverse “liver first” strategy (n = 7). Most patients (92%) received preoperative, interval and/or postoperative chemotherapy. Median overall survival of the entire population was 33.6 months (interquartile range [IQR] 11–92.7 months). Patients undergoing classic surgery had a median overall survival of 40.3 months (IQR 14.9–96.6 months). The 3-year survival rates of the three patient groups were 53% in the classic, 47% in the combined and 58% in the reverse group. The lowest rate of 180-day mortality (9%) was after the classic surgical approach. On a multivariate Cox proportional hazards regression analysis, patient age >60 years (hazard ratio [HR] 2.1, 95% confidence interval [CI] 1.1–3.9; p = 0.018), R2-status (HR 2.08, 95% CI 1.03–4.2; p = 0.040), and >4 liver metastases (HR 2.4, 95% CI 1.2–4.6; p = 0.011) were associated significantly with worse overall survival. CONCLUSIONS In patients undergoing surgical resection for synchronous colorectal liver metastases, promising survival rates could be achieved, irrespective of the chosen surgical strategy. The presence of five or more liver metastases, patient age over 60 years and R2-status were found to be adverse risk factors.